SUNGAI BATU ARCHAEOLOGICAL SITE: SOUTH-EAST ASIA’S OLDEST CIVILISATION TO BE A TOURISM PRODUCT OF KEDAH - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
SUNGAI PETANI, November 2015 – The Director of Centre for Global Archaeological Research (CGAR), Universiti Sains Malaysia (USM), Professor Dato’ Dr. Mokhtar Saidin said, the Kedah state government should introduce Sungai Batu and Sungai Merbok as the main attractions of the state of Kedah in the main agenda for promoting Visit Kedah Year 2016. Furthermore, the latest verified data on Sungai Batu has confirmed that this location is the oldest civilisation site of SouthEast Asia.